Publication tips from NUGSE faculty - Baigazina, Altyn; Gapbassova, Lyazat (NUGSE Research in Education, 1(1), 2016)
Henry Ford once wisely noted, “Coming together is a beginning. Keeping together is progress. Working together is success”. This quote accurately mirrors the team spirit that has inspired and fueled the creation of the first peer-reviewed student-led journal at Nazarbayev University Graduate School of Education. Indeed, the first issue of Research in Education has received tremendous support from NUGSE faculty and the student community, who have willingly taken the initiatives to become peer-reviewers, editors, proofreaders, administrators, designers, writers and authors. This has been a long learning process for all of us, and in this editorial we have collected tips from our contributors for future authors. These recommendations explain how to nail down your research hunch, how to present convincing argumentation in your writing and turn it into a solid paper. In addition, our contributors will help you to clarify what publishing ethics you might want to consider to make your paper look substantial and share their experience on how to navigate through the rigorous publishing process for success.
Keywords: publication tips; NUGSE; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education